Vibrational Spectroscopic Studies of Nitrated Polycyclic Aromatic Hydrocarbons (NPAHs): A Review (1960-2019) - Onchoke, Kefa K. (Vibrational spectroscopy, 2020)
Nitrated polycyclic aromatic hydrocarbons (NPAHs) are ubiquitous in the environment. They are carcinogenic and mutagenic, thus posing great health risks to human health, albeit occurring at one to two orders of magnitude lower than the parent PAHs. Because of their occurrence as mixtures with parent PAHs and the existence of isomers in diverse matrices, analyses of NPAHs and identification is often challenging. Thus, distinguishing spectroscopic signatures of NPAHs in the environment (such as found in particulate matter) poses challenge within different matrices. Often, the nitro-PAH isomers may have overlapping retention times. Analyses of isomers with mass spectrometry, typically yields the same fragmentation patterns. This makes distinguishing isomers in environmental samples challenging. Vibrational spectroscopy offers great potential for distinguishing nitro-PAH isomers. This review discusses the current status of the vibrational spectroscopic information of known 1 - 5 aromatic ring NPAHs. Special attention is devoted to nitro symmetric/asymmetric stretching frequencies. The importance of interpreting vibrational modes highlights the synergy between experimental and theoretical studies. The fundamental principles of quantum chemistry is first briefly presented to highlight the synergy between experiment and theory in the subsequent review sections.